1999
DOI: 10.1559/152304099782330725
|View full text |Cite
|
Sign up to set email alerts
|

Representation and Manipulation of Moving Points: An Extended Data Model for Location Estimation

Abstract: The fields of application of spatio-temporal systems, i.e., systems that must operate with time-varying spatial properties, are vast and heterogeneous. Since it would be difficult to treat such diversity as a whole, we introduce a classification for spatio-temporal systems based on the properties of the represented objects. Building on this classification, we also claim that features of some complex objects can be derived from those of simpler ones, suggesting an evolutionary approach, starting with the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Current work can be found for example in Wolfson (1998), de Caluwe (2004, Petry et al (2005). In Moreira, Ribeiro and Saglio (1999), a data model for representing moving points by a decomposition of a trajectory in several sections is specified. By use of regression techniques, movement within each section is described by a variability function.…”
Section: Qualitative Representation and Reasoning About Space And Timementioning
confidence: 99%
“…Current work can be found for example in Wolfson (1998), de Caluwe (2004, Petry et al (2005). In Moreira, Ribeiro and Saglio (1999), a data model for representing moving points by a decomposition of a trajectory in several sections is specified. By use of regression techniques, movement within each section is described by a variability function.…”
Section: Qualitative Representation and Reasoning About Space And Timementioning
confidence: 99%
“…Sistla et al 1998, Moreira et al 1999, Pfoser and Jensen 1999, Yanagisawa et al 2003. These considerations require that several kind of data must be integrated to have an entire vision of the analysed phenomena that vary in time and space.…”
Section: Models and Techniques In Gis Infrastructuresmentioning
confidence: 99%
“…To cope with the problem of finite sampling in moving object databases (MODs), several researchers, among them (Sistla et al 1998), (Moreira et al 1999), (Trajcevski et al 2004), and (Pfoser et al 2005) have sought to delineate and query the unknown path between two observed locations given a presupposed maximum travel velocity in an unconstrained isotropic travel environment. In line with the advances in MODs, time geographers have also studied the sampling problem extensively using time geography's key concept, i.e.…”
Section: Introductionmentioning
confidence: 99%